2023
DOI: 10.3390/jmse11081603
|View full text |Cite
|
Sign up to set email alerts
|

The Polarized Light Field Enables Underwater Unmanned Vehicle Bionic Autonomous Navigation and Automatic Control

Abstract: In response to the critical need for autonomous navigation capabilities of underwater vehicles independent of satellites, this paper studies a novel navigation and control method based on underwater polarization patterns. We propose an underwater course angle measurement algorithm and develop underwater polarization detection equipment. By establishing the automatic control model of an ROV (Remote Operated Vehicle) with polarization information, we develop a strapdown navigation method combining polarization a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Remote Sens. 2023, 15, 4565 11 of 15 contrast, AOP patterns are more robust in general underwater environments and have better application potential [30,31]. Considering that the Cox-Munk wave model has a good simulation effect under moderate wind speed, the model in this paper has a high accuracy under moderate wind speed.…”
Section: Polarization Patterns Inside Snell's Window Under Wavy Water...mentioning
confidence: 94%
See 1 more Smart Citation
“…Remote Sens. 2023, 15, 4565 11 of 15 contrast, AOP patterns are more robust in general underwater environments and have better application potential [30,31]. Considering that the Cox-Munk wave model has a good simulation effect under moderate wind speed, the model in this paper has a high accuracy under moderate wind speed.…”
Section: Polarization Patterns Inside Snell's Window Under Wavy Water...mentioning
confidence: 94%
“…We find that the AOP patterns are in good agreement with the measured results and the value of AOP is about 0 • when the observed azimuth is 90 • . In contrast, AOP patterns are more robust in general underwater environments and have better application potential [30,31]. Considering that the Cox-Munk wave model has a good simulation effect under moderate wind speed, the model in this paper has a high accuracy under moderate wind speed.…”
Section: Polarization Patterns Inside Snell's Window Under Wavy Water...mentioning
confidence: 96%
“…The accuracy obtained was a 6 m error for every 1km traveled at depths ranging from 2 m to 20 m. A recent study based on deep learning reached geolocation accuracies of 55 km at a depth of 8m and 255 km at a depth of 50 m even in low-visibility waters [ 265 ]. Accurate heading estimation of an autonomous underwater vehicle was recently obtained by merging inertial and polarization information [ 266 , 267 ]. A standard deviation (SD) error of 0.83° was reached here at a depth of 2 m in real oceans in calm seas [ 267 ].…”
Section: Polarized Vision For Robotics Navigationmentioning
confidence: 99%
“…A standard deviation (SD) error of 0.83° was reached here at a depth of 2 m in real oceans in calm seas [ 267 ]. Cheng et al confirmed the deterioration of the heading measurement as a function of depth from 0.93° at a depth of 1 m to 4.07° at a depth of 5 m [ 266 ].…”
Section: Polarized Vision For Robotics Navigationmentioning
confidence: 99%